1998
DOI: 10.1128/iai.66.3.1017-1022.1998
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Nitric Oxide inStaphylococcus aureusInfection in Mice

Abstract: This study was carried out to determine the role of nitric oxide (NO) in Staphylococcus aureus infection in mice. NO production in spleen cell cultures was induced by heat-killed S. aureus. Expression of mRNA of the inducible isoform of NO synthase (iNOS) was induced in the spleens and kidneys of S. aureus-infected mice. When mice were treated with monoclonal antibodies (MAbs) against tumor necrosis factor alpha (TNF-α) or gamma interferon (IFN-γ) before S. aureus infection, the induction of iNOS mRNA expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(29 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…Sasaki et al . 38 detected expression of iNOS mRNA in spleen and kidney of mice 3 hr after intravenous infection with Staphylococcus aureus . Lamarque et al .…”
Section: Discussionmentioning
confidence: 95%
“…Sasaki et al . 38 detected expression of iNOS mRNA in spleen and kidney of mice 3 hr after intravenous infection with Staphylococcus aureus . Lamarque et al .…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, the results obtained in the present study are not unexpected. Similarly, the production of NO by Staphylococcus aureus-stimulated murine spleen cells could be inhibited by an iNOS inhibitor, such as aminoguanidine (22). Stenger et al also demonstrated that l-NIL suppressed the production of NO and iNOS activity in Escherichia coli LPS-stimulated murine macrophages (18).…”
Section: Discussionmentioning
confidence: 97%
“…The net effect of incomplete killing is accumulation of viable intracellular bacteria. Microbicidal killing involves NADPH oxidase stimulation and activation of proteases (Flannagan et al, 2009), as well as nitric oxide (Sasaki et al, 1998), and these macrophage microbicidal mechanisms are enhanced by IFN-γ (Cassatella et al, 1985;Totemeyer et al, 2006). We addressed whether the killing capacity of macrophages could be enhanced by IFN-γ and whether this would prevent intracellular bacterial persistence.…”
Section: Macrophages Capacity For Early Intracellular Killing Of Stapmentioning
confidence: 99%